Crime in the art market - anti-crime measures - Klimczyk, Agata (Journal of Education, Health and Sport, 2017)
The aim of the work is to present selected aspects of crime in the art market and the possibility of counteracting them. The author has used: the method of legal analysis and literature study.Crime in the art market is related to the cultural goods, the author shows what factors have influence to this. It was showed key role of The National Heritage Board of Poland, EU Heritage Legislation.